A Rare Case Report of Undescended Testis: Both on One Side - Tasa, Davoud; Fotoohi, Ahmad; Safarnejad, Farhang; Elyasi, Anvar (Urology Journal, 2020)
Undescended Testis is a medical term that uses for any testis which is not in its normal place (bottom of the scrotum). UDT can be classified as unilateral and bilateral. Unilateral UDT is more common than bilateral UDT. There is a very rare condition in which both testicles are on the same side and have not descended. We report in this article a 3 years old boy by a chief complaint of bilateral testicular mass absence. Diagnostic evaluation has been done but testes was abcent in scrota. Exploring laparoscopy has been done and rare cases of UDT diagnosed, in which both testicles was on left side of the pelvis by two separate spermatic cord. The shorter spermatic cord fixed in the left scrotum and the longer one fixed on the right side. The testis was normal in follow up examinations.